Motivations and Barriers to Help-Seeking Among Female Victims of Intimate Partner Violence in Ghana - Rohn, Emmanuel (Violence against women, 2024)
This study used qualitative data from 30 women in three of Ghana's 16 administrative regions to explore motivations and barriers to help-seeking among victims of intimate partner violence. Results of the thematic analysis showed low reporting to formal support networks, such as the Domestic Violence and Victim Support Unit or the police, with higher preference for informal sources, such as family members and friends. Motivations to seek help included fatigue, severity of abuse, abusive partner's negligence in honoring marital obligations, and trust in family members. Barriers to help-seeking included: fear of divorce, stigmatization, lack of trust in formal support channels, sociocultural norms emphasizing gender role expectations, and family privacy.